Morphologic and seismic features of the Gulf of Gokova, SW Anatolia: evidence of strike-slip faulting with compression in the Aegean extensional regime - Iscan, Yeliz; Tur, Huseyin; Gokasan, Erkan (SPRINGER, 2013)
Recently acquired (2005) multi-beam bathymetric and high-resolution seismic reflection data from the E-W-oriented Gulf of Gokova off SW Anatolia were evaluated in order to assess the uneven seafloor morphology and its evolution in terms of present-day active regional tectonics. Stratigraphically, the three identified seismic units, i.e., the basement, deltaic sediments deposited during Quaternary glacial periods, and modern gulf deposits, are consistent with those observed in previous studies. Structurally, the folds and faults with strike-slip and reverse components have been regionally mapped for the first time. Of these, NE-SW-oriented left-lateral strike-slip faults with compressional components forming the so-called Gokova Fault Zone intersect and displace two WNW-ESE-oriented submarine ridges and deep submarine plains. Thus, strike-slip faults are the youngest major structures in the gulf, and control present-day active tectonism. E-W-oriented folds on the inner and outer shelf, which are generally accompanied by reverse faults, delimit the margins of these submarine ridges, and deform the young basin deposits. These features also reveal the concomitant existence of a compressional tectonic regime. The compressional structures probably represent pressure ridges along left-lateral strike-slip fault segments. However, some E-W-oriented normal faults occur on the northwestern and partly also southern shelf, and along the borders of the adjacent deep submarine plains. They are intersected and displaced by the strike-slip faults. The lower seismicity along the normal faults relative to the NE-SW-oriented strike-slip faults suggests that the former are at present inactive or at least less active.
Keywords: SURROUNDING REGIONS; SOUTHWEST ANATOLIA; ACTIVE TECTONICS; RHODES BASIN; CYPRUS ARCS; SEA; TURKEY; ZONE; EVOLUTION; PLATE; Geology; Oceanography